Case Report: IgA Nephropathy in a Patient With Anti-Transcription Intermediary Factor-1γ Antibody-Positive Dermatomyositis - Zhang, Suo; Chen, Yu-Lan; Liu, Cui-Lian; Xie, Jing-Yi; Sun, Bao-Dong; Liu, Dong-Zhou (Frontiers in Immunology, 2022)
IgA nephropathy (IgAN) is the most common primary glomerulonephritis characterized by IgA deposits in the mesangial area of glomeruli. Connective tissue disorders are some of the most frequent causes of secondary IgAN. Nevertheless, IgAN rarely occurs in idiopathic inflammatory myopathies. The present case study reports on a 58-year-old patient with dermatomyositis with positive anti-transcription intermediary factor (TIF)-1γ antibodies who was diagnosed with IgAN during standard immunosuppressive therapy. Moreover, we have made a systematic review regarding the association of inflammatory myopathies and IgAN. To the best of the authors’ knowledge, this is the first case study describing a patient with anti-TIF1γ antibody-positive dermatomyositis who developed IgAN.